Web based interactive multimedia courseware for history subject - Kang, Kelvin Kai Wen (2015)
The title of this project is Web Based Interactive Multimedia Courseware For History Subject. The problem statements are for the project are the current teaching method in secondary school may hard to attract student’s attention and the multimedia courseware is not much applied in secondary school. The objectives of the project are to develop a web based interactive multimedia courseware for secondary school students, to implement the virtual reality technique into the multimedia courseware, and to enhance the interactivity of multimedia courseware by using latest web technologies. The methodology for the project is ADDIE model, which consists of analyze, design, development, implementation, and evaluation phase. The design of the system is presented in dialogue diagram and storyboard. The system is mainly developed by using HTML5, CSS3, and Javascript. The main software that are used to develop the system are Unity3D Pro 5.0 Version, Autodesk Maya 2015, Adobe Illustrator CC, Adobe Audition CC, Notepad++. The users of the system are 4 Raya class students of SMJK Choong Hua Bidor Perak. The main software that users used to test the system are Google Chrome and Mozilla Firefox. After tested the system, users are required to fill in an questionnaire paper as review and evaluation on the system. Result and discussion on the developed system will be made after this. The constraint and future work of the system will also be stated as part of the result and discussion. Lastly we made a conclusion as a summarization for the entire final year project.